Antimicrobial Peptides Human Beta-Defensin-2 and -3 Protect the Gut During Candida albicans Infections Enhancing the Intestinal Barrier Integrity: In Vitro Study - Fusco, Alessandra; Savio, Vittoria; Donniacuo, Maria; Perfetto, Brunella; Donnarumma, Giovanna (Frontiers in Cellular and Infection Microbiology, 2021)
The intestinal mucosa is composed of a monolayer of epithelial cells, which is highly polarized and firmly united to each other and to the basement membrane thanks to the presence of proteins complexes, called Tight junctions (TJs). Alteration of the mucus layer and TJ causes an increase in intestinal permeability, which can lead to a microbial translocation and systemic disorders. Candida albicans, in addition to its role of commensal, is an opportunistic pathogen responsible for disseminated candidiasis, especially in immunocompromised subjects where the dysbiosis leads to damage of the intestinal mucosal barrier leads to dysbiosi s. In this work, we used a line of intestinal epithelial cells able to stably express the gene that encodes human beta defensin-2 (HBD-2) and -3 (HBD-3) to monitor the invasion of C. albicans in vitro. Defensins are a group of antimicrobial peptides (AMPs) found in different living organisms, and are involved in the first line of defense in the innate immune response against pathogens. The results obtained show that the presence of antimicrobial peptides improves the expression of TJs and increases the TEER Trans Epithelial Electrical Resistence value. In addition, the invasive ability of C. albicans in transfected cells is significantly reduced, as well as the expression levels of genes involved in the apoptotic pathway. Through the study of interaction between antimicrobial peptides and microbiota we will be able in the future to better understand the mechanisms by which they exert the host defense function against intestinal pathogens.